2003
DOI: 10.1128/aac.47.9.2864-2867.2003
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum β-Lactamases in Enterobacteriaceae in Buenos Aires, Argentina, Public Hospitals

Abstract: Resistance to extended-spectrum cephalosporins is often associated with plasmid encoded extended spectrum ␤-lactamases (ESBL). In order to evaluate the prevalence and diversity of ESBLs in enterobacteria in our city, a 1-month-period survey was carried out from April to May 2000. Extended-spectrum-cephalosporinresistant strains, isolated from inpatient clinical specimens other than stools, were collected among 17 participating hospitals. From a total of 427 enterobacterial strains that were collected during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(50 citation statements)
references
References 19 publications
5
43
0
2
Order By: Relevance
“…The presence of CTX-M-15 enzyme in the west of Algeria indicates a countrywide spread of the CTX-M β-lactamases. This situation is comparable to those reported in numerous countries, such as Argentina, Poland and Lebanon where CTX-M-producing Enterobacteriaceae have been described to be endemic [15][16][17][18].…”
Section: Discussionsupporting
confidence: 67%
“…The presence of CTX-M-15 enzyme in the west of Algeria indicates a countrywide spread of the CTX-M β-lactamases. This situation is comparable to those reported in numerous countries, such as Argentina, Poland and Lebanon where CTX-M-producing Enterobacteriaceae have been described to be endemic [15][16][17][18].…”
Section: Discussionsupporting
confidence: 67%
“…Non-TEM-derived ESBLs such as VEB-1 (Kim et al, 2004), CTX-M b-lactamases (CTX-M-1, CTX-M-2, CTX-M-13 and CTX-M-31) (Ho et al, 2005;Karapavlidou et al, 2005) and plasmid-borne AmpC blactamases (CMY-2 and CMY-4) (Verdet et al, 1998;Park et al, 2006) have also been reported infrequently. The prevalence of ESBL-positive strains has been reported at 6.9 % in France , 7.0 % in Argentina (Quinteros et al, 2003), 8.8 % in Italy (Luzzaro et al, 2001) and 9.5 % in the US (Saurina et al, 2000). An outbreak of ESBL-producing P. mirabilis has been reported as a nosocomial infection caused by clonal spread (Nagano et al, 2003;Kim et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These are now considered the most prevalent ESBLs worldwide [11][12][13]. PER-and OXAtype enzymes are more common in P. aeruginosa and Acinetobacter spp., but there have been sporadic reports of PER type ESBLs in Enterobacteriacea originating from France, Argentina and Italy [14][15][16]. Of tremendous import because of their ability to inactivate carbapenems, plasmid-borne KPC enzymes are emerging among K. pneumoniae and other enterobacteria in the Eastern seabord and the heartland of the U.S. and internationally [17].…”
Section: Global Epidemiology Of Enterobacteriaceae-producing Esblsmentioning
confidence: 99%